2015
DOI: 10.1021/acs.jpcb.5b00240
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Cholesterol Does Not Alter Significantly Its Uptake into High-Density Lipoprotein Particles

Abstract: Using replica exchange umbrella sampling we calculated free energy profiles for uptake of cholesterol and one of its oxysterols (7-ketocholesterol) from an aqueous solution into a high-density lipoprotein particle. These atomistic molecular dynamics simulations show that both sterols are readily taken up from the aqueous solution with comparable free energy minima at the surface of the particle of -17 kcal/mol for cholesterol and -14 kcal/mol for 7-ketocholesterol. Moreover, given its preferred position at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The diameter of spherical HDL is approximately 10 nm; therefore, it can be simulated in the same box size as one of the larger discoidal HDLs [4451]. In contrast, the diameters of LDL and VLDL are approximately 20 and 30 nm, respectively.…”
Section: Review Of Simulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The diameter of spherical HDL is approximately 10 nm; therefore, it can be simulated in the same box size as one of the larger discoidal HDLs [4451]. In contrast, the diameters of LDL and VLDL are approximately 20 and 30 nm, respectively.…”
Section: Review Of Simulation Methodologymentioning
confidence: 99%
“…The convergence of free energy profiles can be accelerated by combining umbrella sampling with Hamiltonian REX, whereby windows are allowed to exchange along the reaction coordinate [86, 87]. This technique was used by Karilainen et al [51] to estimate the free energy of uptake of cholesterol and 7-ketocholesterol into α-HDL.…”
Section: Review Of Simulation Methodologymentioning
confidence: 99%
“…Reconstructing the free energy profiles for transfer of cholesterol and an oxysterol (7-ketocholesterol) from the water phase into the HDL particle, they showed that both cholesterol and the oxysterol exhibit comparable minima and localize to the surface of the particle. The authors proposed the surface localization of the oxysterols as a potential mechanism for how oxysterols may be involved in signaling …”
Section: How Do Biomembranes Use Lipids To Store Energy?mentioning
confidence: 99%
“…1265 Oxysterols are oxidized cholesterol derivatives. Since oxidation impairs cholesterol uptake from the cells by HDL and is likely to play a signaling role in cholesterol transport, Karilainen et al 1266 investigated the effect of oxidation on spontaneous cholesterol partitioning into the spherical HDL using REUS all-atom simulations. Reconstructing the free energy profiles for transfer of cholesterol and an oxysterol (7ketocholesterol) from the water phase into the HDL particle, they showed that both cholesterol and the oxysterol exhibit comparable minima and localize to the surface of the particle.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Direct elimination of COPs occurs to protect cell functions. Passive diffusion of COPs occurs spontaneously between cells and extracellular lipid‐containing structures such as LDLs and HDLs (Gelissen et al., 1999; Jessup et al., 2002; Karilainen et al., 2015). In serum, it has been proposed that COPs can be transported by LDLs.…”
Section: Biological Fate Of Dietary Copsmentioning
confidence: 99%